Training on Making Nugget from Lemuru Fish with the Addition of Durian Seed Flour for Stunting Students Mother - Martony, Osldia; Irianti, Evi; Lestrina, Dini (Journal of Saintech Transfer, 2022)
Fish has been widely known for its usage in increasing the growth of children, due to its nutritional contents, such as protein and zinc that can accelerate the increase of children’s heights and weights in the growth period. This community service activity aims to increase fish consumption in elementary school students, especially those suffering from stunting through processing fish into nugget products. The activity carried out was in the form of training on processing fish nuggets using lemuru fish with the addition of durian seed flour to mothers with stunting children at SDN 104255 Paluh Sibaji Village, Pantai Labu District, Deli Serdang Regency. This activity then was continued by offering the students to consume nuggets of lemuru fish durian seeds flour. As a result, the nuggets were considered favorable by the students. The post test involving questions about stunting was conducted to measure the knowledge of each parent in this case. The data showed that parents had high enthusiasm in solving stunting issues due to the increase on average of post test points (8.03), which was two times higher than before (4.81). The outcome of this training was to gain new skills and knowledge to students’ mothers in decreasing stunting cases by serving affordable nutrient-rich food to their children.